2003
DOI: 10.3109/13813450312331342292
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Antigen Stimulation on the Oxidative Stress Parameters in Outbred and Inbred Rabbits

Abstract: The influence of antigen stimulation on the oxidative stress parameters in two groups of rabbits-inbred and outbred were explored by evaluation of the level of lipid peroxidation products (MDA) in the plasma membrane, and the activity of erythrocyte antioxidant defense enzymes superoxide dismutase (SOD) and catalase (CAT). There was not a significant difference between levels of MDA in inbred and outbred rabbits before immunization. However, SOD activity in inbred rabbits was significantly increased in compari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…However, great caution must be exercised in drawing quantitative conclusions, since many unconsidered factors, such as homozygosity, may interfere with the quantitative immune response. Tanchev et al have demonstrated that a simultaneous immunomodulation may elicit different antibody responses [49]. Such a situation could arise from a clinically non-evident bacterial or coccidial gastrointestinal superinfection of the systemically seriously impaired rabbits after primary Toxoplasma infection and parenteral antibiotic therapy.…”
Section: Discussionmentioning
confidence: 98%
“…However, great caution must be exercised in drawing quantitative conclusions, since many unconsidered factors, such as homozygosity, may interfere with the quantitative immune response. Tanchev et al have demonstrated that a simultaneous immunomodulation may elicit different antibody responses [49]. Such a situation could arise from a clinically non-evident bacterial or coccidial gastrointestinal superinfection of the systemically seriously impaired rabbits after primary Toxoplasma infection and parenteral antibiotic therapy.…”
Section: Discussionmentioning
confidence: 98%
“…Additionally, there was a highly significant and direct correlation between SOD activity and sperm morphological abnormality. Since GIV are characterized by high percentage of abnormal morphological spermatozoa which can generate high amount of ROS, the males of this group may be at greater risk of developing pathogenic levels of ROS a phenomenon which causes stimulation of SOD enzyme (55) . This may lead to expect higher SOD activity in spermatozoal homogenate supernatant of GIV to help in overcome the LPO (18) .…”
Section: Extensive Study On the Peroxidation Of Phospholipids In Mammmentioning
confidence: 99%
“…According to recent findings, at least one marker of AOX activity and one marker of oxidative damage should be measured to adequately quantify overall OS (Prior and Cao 1999;Clarkson and Thompson 2000;Cohen and McGraw 2009;Costantini and Verhulst 2009;Selman et al 2012;Christensen et al 2015). Laboratory and field studies have revealed that mounting an immune response can increase oxidative damage and decrease AOX activity (Tanchev et al 2003;Costantini and Moller 2009;Marri and Richner 2015;von Schantz et al 2016). However, despite evidence suggesting that infection risk, OS, and host immune capacity are related, little is known about the temporal consistency of relationships among viral infections, OS markers, and immune function in wild animals.…”
Section: Introductionmentioning
confidence: 99%